In the Shadow of Jakarta City, Migrants and Exploitation in Secangkir Kopi Pahit - Soehadi, Gaston (Komunikator, 2018)
This article examines Secangkir Kopi Pahit (Bitter Coffee, 1985), Teguh Karya’s tenth feature film, in which the film uses a non-linier investigative narrative structure to tell a complex story of an urban migrant coming to live in Jakarta. Unlike his previous films, in Secangkir Kopi, Teguh develops a new and unique filmic storytelling approach (using complex flashback structure in addition to filming location; central character a photographer and reporter obsessed with the city and exposing situations), which arguably produces a reality effect in depicting the growing third world megacity of Jakarta in the early 1980s. Secangkir Kopi Pahit combines and arranges various plots to portray the experience of people living in a late 20th century, third world megacity. The use of a complex narrative form from the beginning puts pressure on the viewer’s capacity to comprehend events in the film.